Measuring institutional quality in ancient Athens - Andreas Bergh; Carl Hampus Lyttkens (Lund University, School of Economics and Management, Department of Economics, 2011)
We use the Economic Freedom Index (Gwartney, Lawson and Norton 2008) to characterise the institutions of ancient Athens in the fourth century BCE. It has been shown that ancient Greece witness improved living conditions for an extended period of time. Athens in the classical period appears to fare particularly well. We find that economic freedom in ancient Athens is on level with the highest ranked modern economies such as contemporary Hong Kong and Singapore. With the exception of the position of women and slaves, Athens scores high in almost every dimension of economic freedom. Trade was highly important even by current standards. As studies of contemporary societies show institutional quality to be an important determinant of economic growth, this may be one factor in the relative material success of the Athenians.
Keywords: N43; N93; O17; P52; 330; institutions; quality; growth; ancient Athens